Andersen's fairy tales - Andersen, H. C. (Hans Christian), 1805-1875.; Shapiro, Ellen Sara, 1950- (New York : Children's Classics, 1999)
A collection of thirty-eight fairy tales by Andersen, including "The Mermaid, " "The Red Shoes, " and "The Swineherd."
Originally published as Faery tales from Hans Andersen in a slightly different form.
" ... edition was prepared with the assistance and advice of Ellen S. Shapiro"--P. xiv.
Keywords: Fairy tales -- Denmark; Children's stories, Danish -- Translations into English; Fairy tales